Optimization of sweet potato (Ipomea batatas var. Bureau) flour substitute in puto - Omadto, Sharon Padernal; Rumbaoa, Rowena Grace O. (2005)
ABSTRACT Sweet potato flour (SPF) was produced utilizing the Bureau variety as a raw material. The FNRI procedure was modified using a High Performance Dehydration System (sandvik dryer). Dehydration at 70°C in 30-40 minutes produced yellow flour. Subjective and objective measurements from repeated production runs revealed that the process was standardized. SPF was used to partially substitute all-purpose flour (APF) in puto. Initial tests showed that SPF substitution at 50% and higher significantly reduced product acceptability. A lower range of substitution showed that 25% appear to be the optimum level wherein sensory and physical characteristics of the product were unaltered.
Thesi (BSFT)--University of the Philippines Diliman.
Keywords: Flour; Sweet potatos